Буковина у правовій системі Румунії (1918–1940 рр.) - Торончук, Іван Желувич (Національний університет "Львівська політехніка", 2012)
У дисертації на підставі аналізу наукової літератури, архівних документів, а також нормативно-правових актів досліджено питання про місце Буковини у правовій системі Румунії (1918–1940 рр.). Проаналізовано передумови та обставини, за яких Буковина була анексована Румунією 1918 р., що в подальшому легалізовано на Паризькій мирній конференції. Висвітлено місце і роль вищих та місцевих органів влади, які діяли в Румунії та на Буковині в міжвоєнний період, розкрито їхню компетенцію, структуру та порядок роботи. З’ясовано зміст, структуру та особливості системи самоврядування на Буковині. Значну увагу приділено висвітленню питань діяльності каральних органів на Буковині (суду, прокуратури, поліції, сигуранци та жандармерії). В диссертации на основе анализа научной литературы, архивных документов, а также нормативно-правовых актов исследуются вопросы о месте Буковины в правовой системе Румынии (1918–1940 рр). Анализируются предпосылки и обстоятельства, при которых Буковина была аннексирована Румынией в 1918 г., что в дальнейшем легализовано на Парижской мирной конференции. Освещены место и роль высших и местных органов власти, действующих в Румынии и на Буковине в межвоенный период, раскрыто их компетенцию, структуру и порядок работы. Выяснены содержание, структура и особенности системы самоуправления на Буковине. Значительное внимание уделено освещению вопросов деятельности карательных органов на Буковине (суда, прокуратуры, полиции, сигуранцы и жандармерии). On the grounds of analysis of scientific literature, archive documents, as well as statutory and legal acts, the dissertation studies issues on the place of Bukovina in the legal system of Romania (1918–1940). Prerequisites and circumstances are being analyzed under which Bukovina was annexed by Romania in 1918 what was furtherly legalized at Paris Peace Conference. Place and role of superior and local governmental authorities acting in Romania and in Bukovina in interwar period are being elucidated, their competence, structure and work order are being shown. The functioning of the system of self-government authorities in Bukovyna, which consisted of two levels – the county and the community ones (city and rural) – has been analyzed according to the Law of Romania of 1918–1940. Their competence covered exceptionally local questions, the majority of which were of economic character; during the interwar periods of time they were transformed into an obedient appendix of the centralized apparatus of the central and local executive power. The process of formation of the Romanian judicial system in Bukovyna has been studied comprehensively, as well as its reformation during the interwar period. It has been established that judicial reforms that took place in the interwar Romania were aimed at the creation of a unified system of general and specialized courts, regulation of the legal status of judicial authorities and the judges, definition of common professional requirements to candidate judges, common requirements to case consideration in the Courts of Appeal and Courts of Review. Analysis of the role of the prosecutor’s office in the system of penal authorities in Bukovyna during the interwar period has been done, and it has been established that statutory regulation of its organization and activity in the land had its own specific character due to the fact that the land had previously been a part of the Austro-Hungarian Empire. Fundamentals of legal organization of the activity of the Romanian police in Bukovyna have been illustrated, as well as the order of its staffing, major directions, forms and methods of activity. It has been established that police reforms passed during the interwar period of time in Romania were aimed at strengthening the police apparatus and its centralization, and provided for the realization of the Romanian Rule at the local level. Peculiarities of functioning of the Romanian political police (siguranţă) in Bukovyna have been revealed, its organization and functioning in the land analyzed. The impact of siguranţă as the main penal authority of Romania on the social and political life in Bukovyna was determined, the major task of which was fighting against anti-Romanian views in the land. Also, the legal status of gendarmery (rural police) in Bukovyna during the time of the Romanian rule has been determined.
Буковина в правовой системе Румынии (1918–1940 гг.)
Bukovina in the Legal System of Romania (1918–1940)
Keywords: міністр-делегат; префект; королівський резидент; громадські ради; примар; суд; прокуратура; поліція; сигуранца; жандармерія; министр-делегат; префект; королевский резидент; общественные советы; примар; суд; прокуратура; полиция; сигуранца; жандармерия; delegate minister; prefect; royal resident; community councils; primar; court; public prosecutor’s office; police; siguranza and gendarmerie